Amino Acid Content and Availability in Low, Medium and High Tannin Sorghum Grain for Poultry - Ebadi, M.R.; Pourreza, J.; Jamalian, J.; Edriss, M.A.; Samie, A.H.; Mirhadi, S.A. (International Journal of Poultry Science, 2004)
In order to assess and determine amino acids profile and availability in different sorghum grain (SG) varieties, three SG varieties including low tannin (0.09%, LTS), medium tannin (0.19%, MTS), and high tannin (0.37%, HTS) were grown in the same location. The grains were analyzed for their proximate analyses, tannin, and amino acids. True amino acid availability (TAAA) was obtained by caecectomized single comb leghorn cockerels and Sibbald`s method. The results showed that the first and the second limiting amino acids in LTS and MTS were methionine and cystine, respectively. Whereas in HTS, lysine (0.166%) was the first and methionine (0.176%) was the second limiting amino acid. Methionine contents in LTS, MTS, and HTS were 0.114%, 0.182%, and 0.176%, respectively. Although crude protein was lower in HTS (10%) than the other SG, histidine, methionine, and isoleucine were higher for HTS as compared to LTS and MTS. TAAA decreased when tannin content increased and all amino acids had a lower availability in HTS than in LTS and MTS (p